Investigation of the Tidal Character in Bawean Island East Java Using Admiralty Method - Luhur Moekti Prayogo; Muhammad Hanif (Jurnal Perikanan dan Kelautan, 2022)
Bawean Island is one of the islands in Gresik Regency, East Java, where almost all its territory is a coastal environment. This region's tidal oceanographic condition is critical because this area has a lot of potential for marine tourism and relatively shallow waters. This study aims to determine the tidal characteristics in the waters of Bawean Island, East Java, using the Admiralty method. This method was chosen because it can calculate the tidal component with only 15 days of data and can be used in various water conditions. The data used is tidal data from the Geospatial Information Agency (BIG) on November 1-15, 2020. From this research, it can be concluded that tidal analysis using the Admiralty method produces nine components, including M2, S2, N2, K1, O1, P1, M4, MS4, and K2. The four components determine the type of tide, namely O1, K1, M2, and S2, with amplitude values of 11.79347, 30.14857, 55.72241, and 63.69851. The calculation with the Formzahl number equation yields a value of 0.3512 (0.25 <F <1.5), which means that the tidal type in Bawean Island, East Java, has a mixed type with a semidiurnal tendency (double daily).